The Liberalization and Management of Capital Flows : An Institutional View. (Policy Papers; Policy Paper ;, 2012)
Capital flows have increased significantly in recent years and are a key aspect of the global monetary system. They offer potential benefits to countries, but their size and volatility can also pose policy challenges. The Fund needs to be in a position to provide clear and consistent advice with respect to capital flows and policies related to them. In 2011, the International Monetary and Financial Committee (IMFC) called for ?further work on a comprehensive, flexible, and balanced approach for the management of capital flows.? This paper proposes an institutional view to underpin this approach, drawing on earlier Fund policy papers, analytical work, and Board discussions on capital flows.